Electrophoretic mobilities of neutral analytes and electroosmotic flow markers in aqueous solutions of Hofmeister salts - Křížek, Tomáš; Kubíčková, Anna; Hladílková, Jana; Coufal, Pavel; Heyda, Jan; Jungwirth, Pavel (Electrophoresis, 2014)
Small neutral organic compounds have traditionally the role of EOF markers in electrophoresis, as they are expected to have zero electrophoretic mobility in external electric fields. The BGE contains, however, ions that have unequal affinities to the neutral molecules, which in turn results in their mobilization. In this study we focused on two EOF markers-thiourea and DMSO, as well as on N-methyl acetamide (NMA) as a model of the peptide bond. By means of CE and all atom molecular dynamics simulations we explored mobilization of these neutral compounds in large set of Hofmeister salts. Employing a statistical mechanics approach, we were able to reproduce by simulations the experimental electrophoretic mobility coefficients. We also established the role of the chemical composition of marker and the BGE on the measured electrophoretic mobility coefficient. For NMA, we interpreted the results in terms of the relative affinities of cations versus anions to the peptide bond.
Keywords: acetamidy; Molecular Dynamics Simulation; Thiourea; roztoky; Electrophoresis, Capillary; Dimethyl Sulfoxide; elektroforéza kapilární; lithium; Lithium; simulace molekulární dynamiky; Osmolar Concentration; elektroosmóza; thiomočovina; Acetamides; Solutions; cesium; Salts; dimethylsulfoxid; osmolární koncentrace; Electroosmosis; Cesium; soli